Social Aspects of India Through the Journey of Ibn Battuta, Entitled Tuhfat al-Nuzzar fi Ghara’ib al-Amsar wa ‘Aja’ib al-Asfar (d. 779AH / 1377 AD) - Mutawaq, Manal Hilal (Journal of Humanities & Social Sciences, 2025)
This research elucidates the social aspects of India as depicted in the travelogue of Ibn Battuta, Tuhfat al-Nuzzar fi Ghara’ib al-Amsar wa ‘Aja’ib al-Asfar. It highlights the prevailing religious beliefs and societal stratifications of that era, along with the distinctive customs, traditions, and culinary practices that characterized Indian society at the time. Furthermore, it delves into the diverse religious festivals and celebrations, the ceremonial rites observed by different faiths, and the royal court rituals that were performed. The study also explores marriage traditions among Indians, demonstrating that Ibn Battuta’s account serves as an invaluable historical source, offering a meticulous and vivid portrayal of these social phenomena.
Keywords: Social aspects; India; Ibn Battuta’s journey